Endoscopic Ultrasound-Guided Enteroenterostomy for Afferent Limb Syndrome. Issue 8 (10th August 2020) - El Bacha, Hicham; Leblanc, Sarah; Bordacahar, Benoit; Brieau, Bertrand; Barret, Maximillien; Savier, Eric; Soubrane, Olivier; Dousset, Bertand; Prat, Frederic
ABSTRACT: Afferent limb syndrome (ALS) is a rare complication of duodenopancreatectomy, resulting from the mechanical obstruction of the afferent limb usually after local malignancy recurrence. Management of ALS (ie, surgery and palliative therapy) is often unsatisfactory. We present 5 cases of endoscopic ultrasound-guided internal drainage of the afferent limb using lumen-apposing metal stents. All procedures were successful, with no related complications; 2 patients had a complete regression of their symptoms, one experienced cholangitis recurrence, and 2 patients died after some weeks because of their malignancies. Endoscopic ultrasound-guided enteroenterostomy offers a convenient and safe palliative solution for patients presenting ALS.